Analisis Kromosom Varietas Kacang Gude (Cajanus cajan (L.) Millspaugh) Asal Pulau Kisar, Maluku Barat Daya (MBD) - Alwi Smith; Kristin Sangur; Eclesia Danisa (Jurnal Biologi Papua, 2021)
Pigeon pea (Cajanus cajan) is one of the biodiversity of Kisar Island, Maluku Barat Daya (MBD). This study aimed to determine the number and size of chromosomes from pigeon pea (C. cajan) from Kisar Island, MBD. The method used for chromosome observation is the squashing method, while for the analysis of the shape and size of chromosomes using the picsart and image raster applications. Data analysis using descriptive analysis with the help of figures and tables. The results showed that the chromosome number of three varieties of pigeon pea (C. cajan) was 2n = 14. The longest chromosome is owned by orange seed varieties that are 9.17 µm, batik color seed varieties are 9.09 μm, the shortest chromosomes are owned by black seed varieties of 8.32 µm. The chromosome length of the three varieties of pigeon pea (C. cajan) varies showing different genome numbers.   Key words: Chromosome; Cajanus cajan; Kisar Island; Maluku Barat Daya.